Systemic jasmonic acid modulation in mycorrhizal tomato plants and its role in induced resistance against alternaria alternata - Nair, A.; Kolet, Swati P.; Thulasiram, H. V.; Bhargava, S. (Plant Biology, 2015)
Tomato plants colonised with the arbuscular mycorrhizal (AM) fungus Glomus fasciculatum show systemic induced resistance to the foliar pathogen Alternaria alternata, as observed in interactions of other AM-colonised plants with a range of pathogens. The role of jasmonic (JA) and salicylic (SA) acid in expression of this mycorrhiza-induced resistance (MIR) against A.alternata was studied by measuring: (i) activity of enzymes reported to be involved in their biosynthesis, namely lipoxygenase (LOX) and phenylammonia lyase (PAL); and (ii) levels of methyl jasmonate (MeJA) and SA. Transcript abundance of some defence genes associated with JA and SA response pathways were also studied. Both LOX and PAL activity increased twofold in response to pathogen application to control plants. AM-colonised plants had three-fold higher LOX activity compared to control plants, but unlike controls, this did not increase further in response to pathogen application. Higher LOX activity in AM-colonised plants correlated with four-fold higher MeJA in leaves of AM-colonised plants compared to controls. Treatment of plants with the JA biosynthesis inhibitor salicylhydroxamic acid (SHAM) led to 50% lower MeJA in both control and AM-colonised plants and correlated with increased susceptibility to A.alternata, suggesting a causal role for JA in expression of MIR against the pathogen. Genes involved in JA biosynthesis (OPR3) and response (COI1) showed six- and 42-fold higher expression, respectively, in leaves of AM-colonised plants compared to controls. AM-colonised plants also showed increased expression of the SA response gene PR1 and that of the wound-inducible polypeptide prosystemin. Our results suggest that the systemic increase in JA in response to AM colonisation plays a key role in expression of MIR against A. alternata.
Keywords: Alternaria alternata; AM colonisation; induced resistance; Methyl jasmonate; salicylhydroxamic acid; Salicylic acid; Solanum lycopersicum